Corporate governance and performance: a comparative study of Shari’ah approved and non-shari’ah approved companies on Bursa Malaysia - Mohamad Ibrahim, Shahul Hameed; A.H, Fatima; Htay, Sheila Nu Nu (Emerald Group Publishing Limited, 2006)
This study examines whether Shari’ah approved companies with majority Muslim directors adopt better corporate governance (CG) than non-Shari’ah approved companies with majority non-Muslim directors and whether the performance of the former is better than that of the latter. The objective of this study is to determine whether religious factor has an influence in adopting corporate governance mechanisms and in performance. Performance of the companies is measured in relation to three perspectives, namely, Shari’ah compliance, environmental performance, and social performance. This study used secondary data and the leading 50 firms were selected from each group based on their market capitalization for the year 2002. The proxies for good corporate governance are CEO non-duality, the proportion of non-executive directors on the board, and the proportion of independent non-executive directors on the board. The proxies used to measure Shari’ah compliance are the ratio of prohibited income to total income and the ratio of prohibited expenses to total expenses. The variables used to measure the environmental and social performance are certification of ISO 14001 and OHsas 18001, respectively. The results generally showed that there is little significant difference between the CG and performance of Shari’ah approved companies with majority Muslim directors and non-Shari’ah approved companies with majority non-Muslim directors, although the former is marginally better for both, in a few instances.